2017
DOI: 10.1097/ogx.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sentinel Lymph Node Biopsy to Lymphadenectomy for Endometrial Cancer Staging (FIRES Trial): A Multicentre, Prospective, Cohort Study

Abstract: (Abstracted from Lancet Oncol 2017;18:384–392) In more than 75% of women with endometrial cancer, the disease is confined to the uterus. Recurrence risk is defined by surgical staging with lymphadenectomy and helps in the decision to give adjuvant treatment to high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 0 publications
8
120
0
6
Order By: Relevance
“…The relevant literature has reported that low- and high-risk factors for pelvic lymph-node metastasis were 1.4–3% and 6.4–23%, respectively [ 2 , 11 ]. The SLN detection in the abdominal aorta was less than 5% [ 19 ]. In addition, the probability that SLN had an abdominal aortic lymph-node transfer was low at 0.8–1%, with a 3% chance of metastatic EC in high-risk patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relevant literature has reported that low- and high-risk factors for pelvic lymph-node metastasis were 1.4–3% and 6.4–23%, respectively [ 2 , 11 ]. The SLN detection in the abdominal aorta was less than 5% [ 19 ]. In addition, the probability that SLN had an abdominal aortic lymph-node transfer was low at 0.8–1%, with a 3% chance of metastatic EC in high-risk patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of lymphedema in the legs was significantly lower after sentinel lymph node mapping as compared to full lymphadenectomy (1.3% vs. 18.1%; p < 0.001) [43]. As mentioned earlier, the FIRES test reports sentinel lymph node mapping sensitivity is higher than 95% [38]. Recently, 2 comparative studies were conducted between two referral centers, the Mayo Clinic (Rochester, MN, USA) and the Memorial Sloan Kettering Cancer Center (New York, USA) [41] [44].…”
Section: Methodsmentioning
confidence: 60%
“…At the Mayo Clinic, total pelvic and para-aortic lymphadenectomy was performed in specific cases considered to have a risk of nodal metastasis (FIGO grade 3 and/or primary tumor diameter > 2 cm) [44]. Increasing evidence indicated that sentinel lymph node mapping does not affect the outcomes as compared to patients with full node dissection [38] [44] [45]. Buda et al confirmed data and reported higher prevalence of positive lymph nodes in-patient undergoing sentinel lymph node mapping as compared to conventional lymph node dissection group (16.7% and 7.3% of patients with positive pelvic lymph nodes, in sentinel node mapping and lymphadenectomy groups respectively; p = 0.002) [46].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations